2015
DOI: 10.1186/s40168-014-0066-1
|View full text |Cite
|
Sign up to set email alerts
|

VizBin - an application for reference-independent visualization and human-augmented binning of metagenomic data

Abstract: BackgroundMetagenomics is limited in its ability to link distinct microbial populations to genetic potential due to a current lack of representative isolate genome sequences. Reference-independent approaches, which exploit for example inherent genomic signatures for the clustering of metagenomic fragments (binning), offer the prospect to resolve and reconstruct population-level genomic complements without the need for prior knowledge.ResultsWe present VizBin, a Java™-based application which offers efficient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
385
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(406 citation statements)
references
References 24 publications
(35 reference statements)
16
385
0
Order By: Relevance
“…The impact of delivery mode and infant feeding history on the gut microbiota may, therefore, be lost after the first years of life, although it is still unclear exactly when (Penders et al ., 2006; Biasucci et al ., 2010). Gut microbiota composition has been reported to begin to converge toward an adult‐like microbiota by the end of the first year of life and fully resemble the adult microbiota by 2.5 years of age (Clemente et al ., 2012), although other studies have shown that the microbiota of children up to 4 years of age differs from that of adults (Kulka et al ., 2013; Hollister et al ., 2015), suggesting that conversion to an ‘adult‐like’ microbiota may be a long and gradual process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The impact of delivery mode and infant feeding history on the gut microbiota may, therefore, be lost after the first years of life, although it is still unclear exactly when (Penders et al ., 2006; Biasucci et al ., 2010). Gut microbiota composition has been reported to begin to converge toward an adult‐like microbiota by the end of the first year of life and fully resemble the adult microbiota by 2.5 years of age (Clemente et al ., 2012), although other studies have shown that the microbiota of children up to 4 years of age differs from that of adults (Kulka et al ., 2013; Hollister et al ., 2015), suggesting that conversion to an ‘adult‐like’ microbiota may be a long and gradual process.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is recognized that the gut microbiota has the potential to change along with the development of its host, information regarding the structure and function of the microbiome in children remains limited (Hollister et al ., 2015). We hypothesized that an aberrant gut microbiota composition and activity might contribute to the development of childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the resilience of the gut microbiota, the gut microbiome exhibits functional redundancy, which guarantees that the key functions are maintained for normal gut functioning [28,30]. These key functions are conserved among individuals and this set of genes is normally referred to as a core microbiome [1,31].…”
Section: The Gut Microbiotamentioning
confidence: 99%